Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi dalam Membayar Pajak Kendaraan Bermotor di Muaro Jambi - Anam, Khairul; Habriyanto, Habriyanto (ARZUSIN, 2025)
Motor vehicle tax is a significant source of regional revenue; however, the compliance level of individual taxpayers in Muaro Jambi remains low, necessitating an analysis of the factors influencing such compliance. This study aims to examine the influence of taxpayer awareness and tax sanctions on the compliance of individual taxpayers in paying motor vehicle taxes in Muaro Jambi during the 2021–2023 period. The research employs a quantitative method, with data collected through questionnaires distributed to a number of motor vehicle taxpayers as the research sample. The data were analyzed using multiple linear regression to test the effect of the independent variables—taxpayer awareness and tax sanctions—on the dependent variable, taxpayer compliance. The results show that taxpayer awareness has a positive and significant effect on compliance, where understanding the benefits and obligations of taxation encourages greater compliance. Additionally, tax sanctions also have a significant impact, indicating that strict and consistent enforcement of penalties can enhance taxpayer compliance. The study concludes that awareness and tax sanctions jointly play a crucial role in improving compliance with motor vehicle tax obligations. The implications suggest that local governments and relevant agencies need to strengthen tax education and ensure consistent enforcement of sanctions to increase public awareness and compliance in tax payments.